Islamic Historiography: By Chase F. Robinson (Cambridge: Cambridge University Press, 2003. 264 pages.) (American Journal of Islam and Society, 2004)
In this introduction to the large, unwieldy, and complex topic of Islamic historiography,the author has limited himself to historical works written inArabic, primarily in the central Islamic lands, before 1500. This choice canbe justified in that the field’s formative works written early on in Iraq, Iran,Egypt, and Syria and all in Arabic, served as models for historians writinglater on in peripheral regions and in other languages. Nevertheless, it is a bowto convenience and necessity, given the vast amount of material involved. Asa result, the Arabic historiography of North Africa, Sub-Saharan Africa, andother peripheral regions are largely ignored, as are the Turkish histories of theOttoman Empire and the Persian histories of Iran, Central Asia, and India.Within these admitted and understandable limitations, the book provides anexcellent thematic overview, while, at the same time, introducing the readerto some of the Islamic world’s most fascinating histories and historians.This book is divided into three parts, including ten chapters and aconclusion. A glossary, five plates of manuscript folios, three maps, twochronologies of prominent historians, and suggestions for further readingcontribute to making this a useful and accessible text.In part 1, chapters 1-4, Robinson presents a tripartite typology of historicalworks: chronography, biography, and prosopography. These are idealtypes, which serve as broad categories within which to classify a huge bodyof texts. Chronography refers to annals, works organized into year-by-yearsections; biography refers to texts that treat the lives of famous or exemplaryindividuals; and prosopography refers primarily to biographical dictionaries,works in which biographical notices are devoted to large numbers of individualswho all belonged to a particular scholarly or professional group. Allof these types of historical works, Robinson writes, had emerged by theninth century and were consolidated by the early tenth century. The end ofthis formative period was characterized by large synthetic works, such asAbu Ja`far al-Tabari’s History of Messengers and Kings. In part because ofsuch works, many earlier historical monographs, including the works ofsuch historians as Abu Mikhnaf and al-Mada’ini, were abandoned by the traditionas unnecessary ...